A case of low-grade mucoepidermoid carcinoma with bone invasion of the mandible arising from the sublingual gland showing a MAML2 Gene Split. Issue 2 (March 2022) - Yamada, Hirohisa; Ichimura, Norihisa; Yamamoto, Noriyuki; Okumura, Yuki; Nishikawa, Masaya; Yamaguchi, Satoshi; Uejima, Shinji; Hibi, Hideharu
Abstract: A mucoepidermoid carcinoma (MEC) is the most common malignant tumor of the salivary gland. It frequently occurs in the parotid and minor salivary glands, but rarely originates from the sublingual gland. We report a case of a low-grade MEC arising from the sublingual gland with a MAML2 gene split on fluorescence in situ hybridization (FISH). In May 2017, a 57-year-old woman visited our hospital with left-sided tongue numbness and swelling of the floor of the mouth. We performed a biopsy, but the lesion was indistinguishable from malignant tumors such as MEC, or atypical epithelium associated with inflammation. Subsequently, an MEC was suspected based on computed tomography findings of invasion into the bone marrow and destruction of the outer margin of the mandibular cortex. In July 2017, tracheostomy, bilateral supraomohyoid neck dissection, combined resection of the floor of the mouth and reconstruction of the free peroneal composite flap with a vascular handle were performed under general anesthesia. Although perineural and mandibular invasion was observed, the tumor was considered a low-grade malignancy based on histopathological findings. Furthermore, a split signal in the MAML2 gene was detected on detailed molecular analysis using FISH. No recurrence was observed more than three years after definitive surgery. The presence of the MAML2 fusion gene is useful for the accurate diagnosis of an MEC. Overall, we report a rare case of an MEC in the sublingual gland with mandibular invasion where MAML2 fusion was confirmed.